High Ohmic Reactor as a Shunt Limiter (HOR-SL) Method for Ferroresonance Elimination in the Distribution System - Alaa M. Abdel-Hamed; Mohamed M. El-Shafhy; Ebrahim A. Badran (IEEE Access, 2022)
Aberrant system oscillations cause electrical network components to malfunction in a catastrophic way. Additionally, this results in saturation of the ferromagnetic core components. These variables cause a significant increase in voltage and/or current, as well as aberrations in the waveforms of voltage and current. The contribution of Distributed Generation (DG), to the decrease in ferroresonance investigation in the distribution zone, is discussed in this paper. A new method to reduce ferroresonance using the High Ohmic Reactor (HOR) as a Shunt Limiter (SL) is presented. It is based on the measurements of the negative-sequence components. The proposed HOR-SL reduced the ferroresonance occurrence in the Distribution System (DS) by a time value of no more than 23 milliseconds. The proposed HOR-SL method is compared with the Series Resistance (SR) and Series Tuned LC Limiter (STLCL) methods. The results obtained using the proposed HOR-SL are better than the ones obtained using SE and STLCL. In terms of the voltage and the time taken to mitigate the ferroresonance. The ferroresonance phenomenon is modelled with the help of the PSCAD/EMTDC software. The results obtained demonstrated the effectiveness of implementing the suggested HOR-SL for suppressing ferroresonant oscillations to restore the original state of stability of the distribution network. Case studies strongly proved the effectiveness and robustness of the proposed method in reducing ferroresonance oscillations and maintaining the security of the electrical components in the distribution network.